Immune responses against enterovirus A71 infection: Implications for vaccine success. (1st August 2019) - Aw‐Yong, Kam Leng; NikNadia, Nik Mohd Nasir; Tan, Chee Wah; Sam, I‐Ching; Chan, Yoke Fun
Summary: Enterovirus A71 (EV‐A71) from the Picornaviridae family is an important emerging pathogen causing hand, foot, and mouth disease (HFMD) outbreaks worldwide. EV‐A71 also caused fatal neurological complications in young children especially in Asia. On the basis of seroepidemiological studies from many Asian countries, EV‐A71 infection is very common. Children of very young age are particularly vulnerable. Large‐scale epidemics that occur every 3 to 4 years are associated with accumulation of an immunologically naive younger population. Capsid proteins especially VP1 with the presence of major B‐ and T‐cell epitopes are the most antigenic proteins. The nonstructural proteins mainly contribute to T‐cell epitopes that induce cross‐reactive immune responses against other enteroviruses. Dominant epitopes and their neutralization magnitudes differ in mice, rabbits, and humans. Neutralizing antibody is sufficient for immune protection, but poorer cellular immunity may lead to severe neurological complications and deaths. Some chemokines/cytokines are consistently found in severely ill patients, for example, IL‐6, IL‐10, IL‐17A, MCP‐1, IL‐8, MIG, IP‐10, IFN‐γ, and G‐CSF. An increase in white cell counts is a risk factor for severe HFMD. Recent clinical trials on EV‐A71 inactivated vaccine showed >90% efficacy and a robust neutralization response that was protective, indicating neutralizing antibody correlates for protection. No protection against other enteroviruses was observed. A comprehensive understanding of the immune responses to EV‐A71 infection will benefit the development of diagnostic tools, potential therapeutics, and subunit vaccine candidates. Future development of a multivalent enterovirus vaccine will require knowledge of correlates of protection, understanding of cross‐protection and memory T‐cell responses among enteroviruses.